“Did we tell you…?” Things new administrators need to know - Wendy G Troxel; Stacey Jones Bock; Amy Hurd; Deborah Garrahy (Academic Chairpersons Conference Proceedings, 2015)
A panel of tenured professors who transitioned to administrative positions within the last two years, will provide insights into the most important things new leaders need to know in order to be successful.
Keywords: Leadership; Transition; Communication; Networking